Osteochondral Autologous Transfer Combined With Valgus High Tibial Osteotomy: Long-Term Results and Survivorship Analysis. (October 2013) - Minzlaff, Philipp; Feucht, Matthias J.; Saier, Tim; Schuster, Tibor; Braun, Sepp; Imhoff, Andreas B.; Hinterwimmer, Stefan
Background: Deep osteochondral defects of the medial femoral condyle in young and active patients are a serious condition that might lead to early osteoarthritis of the knee joint. Concomitant varus malalignment most likely promotes this process because of overloading of the medial compartment. Osteochondral autologous transfer (OAT) combined with valgus high tibial osteotomy (HTO) might therefore be a comprehensive solution to preserve long-term knee function in these patients. Purpose: To evaluate clinical long-term results and analyze survival rates (conversion to knee joint arthroplasty) after combined OAT and valgus HTO in young and active patients with symptomatic osteochondral defects of the medial femoral condyle and concomitant varus malalignment. Study Design: Case series; Level of evidence, 4. Methods: Between 1998 and 2008, combined OAT and valgus HTO was performed in 86 patients with deep osteochondral defects of the medial femoral condyle and concomitant varus malalignment >2°; 74 patients (86%) were available for follow-up evaluation. The mean age of patients was 38 years, and the mean follow-up time was 7.5 years. Knee function was assessed using the Lysholm score, and pain intensity was measured using the visual analog scale (VAS). The survival rates of this combined procedure were evaluated. Failure was defined as conversion to knee joint arthroplasty during the follow-up period. Results: Adjusted to follow-up time, the Lysholm score showed a mean increase of 33 points (95% CI, 27.1-39.4; P < .001) from 40 to 73, representing a significant improvement compared with preoperatively. The VAS score decreased by a mean of 4.8 points (95% CI, 4.1-5.5; P < .001) from 7.5 to 2.7, and 93% of the patients were satisfied with the results of the operative procedure. Mean survival rates were 95.2% ± 2.7% at 5 years, 93.2% ± 3.3% at 7 years, and 90.1% ± 4.4% at 8.5 years after surgery. Conclusion: Combined OAT and valgus HTO is an option to successfully treat patients with deep osteochondral defects of the medial femoral condyle and concomitant varus malalignment. Significantly improved knee function, decreased pain intensity, and a high survivorship rate can be expected up to 8.5 years postoperatively.